Клиничко-епидемиолошки карактеристики на тироидните карциноми и значењето на експресија на транскрипти за тумор специфични гени кај диференцирани карциноми - Маказлиева, Тања (Медицински факултет, УКИМ, Скопје, 2018)
INTRODUCTION Thyroid carcinomas (TC) comprise a spectrum of different tumors with wide range of biological behavior and prognosis. Aetiology involved in the development of TC is multifactorial and includes external influences, as well as constitutional predispositions and genetic etiological factors. TC are detected in 5%-10% from all diagnosed thyroid nodules, according to literature data. According to histopathological features TC are grouped in neoplasm originating from epithelial and non-epethelial cells, but in the clinical practice tumors from follicular epithelial cell origin predominate. This group of tumors can be further divided into differentiated TC, poorly differentiated and undifferentiated TC. Medullary thyroid carcinomas originating from neuroendocrine calcitonin-producing C-cells are represented less frequently. Very rare forms of primary thyroid neoplasm are thyroid lymphomas arising from intrathyroidal lymphatic tissue and thyroid sarcomas, developing probably from cells of the intrathyroidal connective tissue. Molecular mechanisms involved in the pathogenesis of TC can be divided into genetic and epigenetic alterations. Genetic alterations can also be classified as nuclear genetic mutations, genetic rearrangements and loss of heterogeneity, while epigenetic changes can be DNA metilation, histone modification and genetic silencing through microRNA. OBJECTIVES It was our aim to analyze the epidemiological, demographic and clinical features of TC in R. Macedonia according to histopathological type for the period 1999 - 2015 and to create regional thyroid cancer register. In addition we wanted to compare the epidemiological and clinical features of TC from previous studies 1966 - 1988, during introduction of the first iodine prophylaxis programme with 10 mg KJ/1 kg salt, with data from 1999 - 2015 when iodine supplementation programme was introduced with 20-30 mg КЈО3/1 kg salt. The objective of our second study was to introduce and apply a method for determination of thyroid tumor specific transcripts in peripheral blood samples, more exactly expression of mRNA-Tg and mRNATSHR, and to analyze and compare results obtained in healthy controls with those of thyroid carcinoma patients as well as to correlate results from RT-PCR with serum thyroglobulin levels and with findings from 131I - whole body scan and neck ultrasound. RESULTS Our analysis revealed continuous trend of increase in incidence rate of thyroid carcinomas in our population, compared with previous data from 1966 - 1988; the greatest increase in incidence rate was recorded for the period 2011 - 2015. Average incidence rate for the period of 17 years (1999 - 2015) in our country was 1,22/105. The increase in incidene rate was mainly due to increase of papillary thyroid carcinoma (PTC) and according to previous data (1966 - 1988) referring to R. Macedonia, there has been a remarkable redistribution among different histopathological types with a reduced number of anaplastic (ATC) and follicular thyroid carcinoma (FTC) cases at the expense of an increased number of PTC, and change of aggressive with more indolent variants of TC. This change in frequency of different histopathological types is probably due to iodine supplementation programme in R. Macedonia and a similar effect was also observed in other countries after iodination. Cox proportional model showed four significant predictors for survival: age, enlarged neck lymph nodes at initial examination, total received 131I - therapy dose and histopathological type of tumor. Age >45 years compared to ≤45 years was associated with significantly increased probability (p<0.05) for cancer specific mortality by 42.9%/month and histopathological type – follicular carcinoma compared to papillary carcinoma was associated with significantly increased probability (p<0.05) for cancer specific mortality by 46.2%/month. Our analysis showed that with simple, repeatable assay it is possible to detect expression of thyroid tumor specific transcripts in peripheral blood. Relative expression showed a statistically significant difference between two groups with incomplete response to treatment and excellent response group and healthy controls. Expression of transcripts for both genes was detected in sampes of almost all healthy controls (except in 3) and in patients with excellent response to treatment, who were previously treated with total thyroidectomy and received radioiodine ablation and have low (<0.2 ng/ml) sTg levels and absence of elements for persistent disease on ultrasound (US) and whole body scan (WBS). This finding may be due to illegitimate transcription in lymphocytes, fibroblasts and other cells. Besides these facts, detected expression was significantly lower in this group compared to patients with persisting disease. CONCLUSIONS Our study revealed a continuous trend of increase in incidence rate of TC in our population. This increase may be partly due to improved diagnostics, however evironmental influences could not be excluded. We have detected a significant reduction in aggressive forms of TC (ATC and FTC) on account of increase of more indolent type of PTC and we can conclude that this is due to introduction of iodine prophylaxis progamme, as similar effects were detected in other populations after introduction of iodine supplementation. The analysis showed that tumor dimension at initial examination and histopathological type of the tumor are two independent prognostic factors of survival rate. Our study results obtained in measurement of expression of tumor specific transcripts in peripheral blood have indicated that it could be a useful laboratory test in monitoring patients with DTC, but further development of absolute quantification method, generation of standard curve and involvement of larger cohort of subjects is necessary for exact evaluation of sensitivity and specificity of the method.
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Оливија Васкова.
Keywords: Thyroid carcinomas, epidemiology, mRNA-TSHR expression, mRNATg expression